Mirror roller and preparation process thereof
By using alloy steel seamless steel pipes and modified nano-titanium carbide-doped nickel-chromium-cobalt surfaces in the preparation process of mirror rollers, the problem of insufficient wear resistance and corrosion resistance of existing mirror rollers is solved, and a higher level of Abrasion resistance and corrosion resistance.
Patent Information
- Application Number
- CN202411562185.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
AI Technical Summary
In the rolling and pressing process, existing mirror rollers have problems such as poor calendering effect and poor durability, especially insufficient wear resistance and corrosion resistance.
The alloy steel seamless steel pipe is used as the outer roller, combined with Q345 as the inner cylinder and alloy steel as the shaft sleeve, and after heat treatment, grinding and electroplating, a modified nano-titanium carbide-doped nickel-chromium-cobalt surface is formed to improve the mirror roller hardness and wear resistance.
The wear resistance and corrosion resistance of the mirror roller are significantly improved, making it have green and environmentally friendly, good mechanical strength, high wear resistance and corrosion resistance.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of mirror surface rollers, in particular to a mirror surface roller and a preparation process thereof. Background Art
[0002] Mirror rollers are often used in the rolling and pressing processes in the printing and dyeing, leather, plastic, papermaking, metallurgy and other industries. In reality, mirror rollers are mostly prepared by chrome plating on seamless steel pipes. Therefore, the quality and performance of mirror rollers are closely related to the chromium layer on the surface.
[0003] With the continuous development of science and technology, the quality requirements for mirror rollers are also increasing. The mirror rollers on the existing market have shortcomings such as poor calendering effect and poor durability. In order to improve the durability of the mirror rollers, the surface of the mirror rollers needs to have sufficient hardness and wear resistance. Summary of the invention
[0004] The object of the present invention is to provide a mirror roller and a preparation process thereof to solve the problems in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] The preparation process of the mirror roller comprises the following steps:
[0007] S1: alloy steel seamless steel pipe is used as the outer roller, Q345 is used as the inner cylinder, alloy steel is used as the shaft sleeve, the inner cylinder and the outer roller are welded to the shaft sleeve respectively, heat treated, and machined to obtain the mirror roller base;
[0008] S2: Grinding, polishing, washing, alkali washing, acid washing, and ultrasonic washing the mirror roller base to obtain a pre-treated base;
[0009] S3: placing the pretreated substrate into an ionic liquid pre-plating solution, performing pre-plating treatment, and obtaining a pre-plated substrate;
[0010] S4: placing the pre-plated base component into an ionic liquid electroplating solution containing composite nano-titanium carbide, and performing electroplating to obtain a base component;
[0011] S5: The base member is subjected to ion nitriding treatment, and then subjected to plasma electrolytic polishing and drying to obtain a mirror surface roller.
[0012] Furthermore, the working conditions of the heat treatment are: keeping at 870°C for 1 h, then cooling to 270°C for 12 h, and heating to 550°C for 30 min.
[0013] Furthermore, the working conditions of the ion nitriding treatment are: first, hydrogen is introduced for sputtering for 30 minutes, then nitrogen and hydrogen are introduced in a volume ratio of 1:3, the furnace pressure is 420 Pa, the temperature is 420°C, the time is 2 hours, and the furnace is cooled.
[0014] Furthermore, the working conditions of plasma electropolishing are: polishing voltage is 280V, electropolishing liquid temperature is 75°C, time is 2min, and diving depth is 15cm; the composition of the electropolishing liquid is: deionized water as solvent, containing 1mol / L phosphoric acid, 0.3mol / L methanol, and 5g / L sodium dodecyl sulfate.
[0015] Furthermore, the composition of the ionic liquid pre-plating solution is: choline chloride-ethylene glycol ionic liquid as solvent, which contains 0.1 mol / L nickel chloride, 0.12 mol / L chromium chloride, 0.18 mol / L cobalt chloride, and 1.8 g / L lactic acid; the composition of the ionic liquid electroplating solution is: choline chloride-ethylene glycol ionic liquid as solvent, which contains 0.1 mol / L nickel chloride, 0.21 mol / L chromium chloride, 0.1 mol / L cobalt chloride, 2 g / L lactic acid, and (3-5) g / L composite nano-titanium carbide.
[0016] Furthermore, the choline chloride-ethylene glycol ionic liquid is prepared by compounding choline chloride and ethylene glycol in a molar ratio of 1:3.
[0017] Furthermore, the working conditions of the pre-plating treatment are: current density 2mA / cm 2 , temperature is 75-80℃, time is 60min; electroplating working conditions are: current density 2mA / cm 2 , temperature is 75-80℃, time is 90min.
[0018] Further, the preparation of modified nano-titanium carbide includes the following steps:
[0019] (1) mixing nano titanium dioxide, carbon black and nano boron carbide, ball milling, pre-pressing, gradient heating, furnace cooling, crushing and ball milling to obtain composite nano titanium carbide;
[0020] (2) Mix composite nano-titanium carbide and N,N-dimethylformamide, add a mixed solution of lanthanum nitrate hexahydrate, cerium nitrate, and N,N-dimethylformamide, add a mixed solution of terephthalic acid and N,N-dimethylformamide, transfer the mixture into a reaction kettle, keep the mixture at 108-112° C. for 44-48 hours, cool, filter, wash, and dry to obtain modified nano-titanium carbide.
[0021] Furthermore, the mass ratio of nano-titanium dioxide, carbon black and nano-boron carbide is 3.1:6.2:1; the working conditions of pre-pressing are: pressure of 100 MPa, time of 1 min; the working conditions of gradient temperature treatment are: in argon atmosphere, keep warm at 1145-1155°C for 85-95 min, then heat to 1445-1455°C and keep warm for 25-35 min.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The invention provides a mirror roller and a preparation process thereof. Through process and component design, a green and environmentally friendly mirror roller with good mechanical strength, high wear resistance and corrosion resistance is prepared.
[0024] In order to improve the durability of the mirror roller, the present invention selects an alloy steel seamless steel pipe as a base material, and uses a green, environmentally friendly, conductive, and highly stable choline chloride-ethylene glycol ionic liquid as an electroplating solvent. A nickel-chromium-cobalt coating is first pre-plated on the surface of the base as a transition layer, and then electroplating is continued on the transition layer to generate a modified nano-titanium carbide-doped nickel-chromium-cobalt surface, giving the mirror roller a gradient hardness, thereby greatly improving the wear resistance and corrosion resistance of the mirror roller; wherein the modified nano-titanium carbide is a composite titanium carbide synthesized by a carbon thermal reduction reaction using nano-titanium dioxide as a titanium source to form a high-purity, uniformly mixed titanium boride-titanium carbide composite ceramic nano-powder, and then a lanthanum and cerium double rare earth metal organic framework is in situ grown on the composite titanium carbide by a solvent thermal method, thereby improving the movement rate of the modified nano-titanium carbide in the ionic liquid, improving the uniformity of its dispersion on the coating, and improving the uniformity of the coating.
[0025] In order to further improve the corrosion resistance and wear resistance of the mirror roller, the base member after electroplating is subjected to nitriding treatment, and clean, efficient, and workpiece-small deformation ion nitriding is selected for treatment. However, in the existing process, the ion nitriding temperature is usually higher than 450°C, which easily leads to the precipitation of chromium nitrides and reduces the corrosion resistance of the substrate. The existing low-temperature ion nitriding has problems such as low nitriding efficiency and long nitriding time, which is not conducive to the promotion of its process. In the present invention, because the modified nano-titanium carbide introduced during electroplating contains titanium, lanthanum, and cerium, among which titanium is a strong nitride-forming element, the formation of chromium nitrides will be inhibited during the ion nitriding process, thereby ensuring the improvement of the corrosion resistance of the base member, and at the same time synergizing with the rare earth lanthanum and cerium to improve the nitriding efficiency, so that the hardness, wear resistance and corrosion resistance of the mirror roller can be quickly improved, which is conducive to its market promotion.
[0026] In order to improve the mirror gloss of the mirror roller and reduce the surface roughness of the mirror roller, plasma electrolytic polishing is used to fine-tune the surface of the mirror roller. By controlling its process parameters, the surface finish of the mirror roller is significantly improved to meet the demand for high-quality surface of the mirror roller in engineering applications, thereby extending the service life of the mirror roller. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] It should be noted that if the embodiments of the present invention involve directional indications such as up, down, left, right, front, and back, the directional indication is only used to explain a specific posture such as the relative position relationship between the components, the movement status, etc. If the specific posture changes, the directional indication will also change accordingly. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.
[0029] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention, and are not used to limit the present invention.
[0030] Embodiment 1: The preparation process of the mirror surface roller comprises the following steps:
[0031] S1: alloy steel seamless steel pipe is used as the outer roller, Q345 is used as the inner cylinder, alloy steel is used as the shaft sleeve, the inner cylinder and the outer roller are welded to the shaft sleeve respectively, heat treated, and machined to obtain the mirror roller base;
[0032] The working conditions of heat treatment are: keep at 870℃ for 1h, then cool to 270℃ for 12h, and heat to 550℃ for 30min;
[0033] S2: Grinding, polishing, washing, alkali washing, acid washing, and ultrasonic washing the mirror roller base to obtain a pre-treated base;
[0034] S3: placing the pretreated substrate into an ionic liquid pre-plating solution, performing pre-plating treatment, and obtaining a pre-plated substrate;
[0035] The composition of the ionic liquid pre-plating solution is: choline chloride-ethylene glycol ionic liquid as solvent, wherein the solvent contains 0.1 mol / L nickel chloride, 0.12 mol / L chromium chloride, 0.18 mol / L cobalt chloride, and 1.8 g / L lactic acid;
[0036] The working conditions of the pre-plating treatment are: current density 2mA / cm 2 , temperature is 75℃, time is 60min;
[0037] Choline chloride-ethylene glycol ionic liquid choline chloride and ethylene glycol are compounded in a molar ratio of 1:3;
[0038] S4: placing the pre-plated substrate into an ionic liquid electroplating solution containing modified nano-titanium carbide, and performing electroplating to obtain a substrate;
[0039] The composition of the ionic liquid electroplating solution is: choline chloride-ethylene glycol ionic liquid as solvent, wherein there are 0.1 mol / L nickel chloride, 0.21 mol / L chromium chloride, 0.1 mol / L cobalt chloride, 2 g / L lactic acid, and 3 g / L composite nano titanium carbide;
[0040] The working conditions of electroplating treatment are: current density 2mA / cm 2 , temperature is 75℃, time is 90min;
[0041] The preparation of the modified nano titanium carbide comprises the following steps:
[0042] (1) mixing nano titanium dioxide, carbon black and nano boron carbide, ball milling, pre-pressing, gradient heating, furnace cooling, crushing and ball milling to obtain composite nano titanium carbide;
[0043] The mass ratio of nano-titanium dioxide, carbon black and nano-boron carbide is 3.1:6.2:1; the working conditions of pre-pressing are: pressure of 100MPa, time of 1min; the working conditions of gradient heating treatment are: in argon atmosphere, keep at 1145℃ for 95min, then heat to 1445℃ for 35min;
[0044] (2) 2 g of composite nano-titanium carbide and 30 mL of N,N-dimethylformamide were mixed, 1 mmol of lanthanum nitrate hexahydrate, 1 mmol of cerium nitrate, and 25 mL of N,N-dimethylformamide were added, and 3 mmol of terephthalic acid and 25 mL of N,N-dimethylformamide were added. The mixture was transferred into a reaction kettle, kept at 108° C. for 48 h, cooled, filtered, washed, and dried to obtain modified nano-titanium carbide;
[0045] S5: performing low-temperature ion nitriding treatment on the base member, and then performing plasma electrolytic polishing, and drying to obtain a mirror roller;
[0046] The working conditions of low-temperature ion nitriding treatment are: first, hydrogen is introduced for sputtering for 30 minutes, then nitrogen and hydrogen are introduced in a volume ratio of 1:3, the furnace pressure is 420Pa, the temperature is 420℃, the time is 4h, and the furnace is cooled;
[0047] The working conditions of plasma electropolishing are: polishing voltage is 280V, electropolishing liquid temperature is 75℃, time is 2min, diving depth is 15cm; the composition of electropolishing liquid is: deionized water as solvent, containing 1mol / L phosphoric acid, 0.3mol / L methanol, and 5g / L sodium dodecyl sulfate.
[0048] Embodiment 2: The preparation process of the mirror surface roller comprises the following steps:
[0049] S1: alloy steel seamless steel pipe is used as the outer roller, Q345 is used as the inner cylinder, alloy steel is used as the shaft sleeve, the inner cylinder and the outer roller are welded to the shaft sleeve respectively, heat treated, and machined to obtain the mirror roller base;
[0050] The working conditions of heat treatment are: keep at 870℃ for 1h, then cool to 270℃ for 12h, and heat to 550℃ for 30min;
[0051] S2: Grinding, polishing, washing, alkali washing, acid washing, and ultrasonic washing the mirror roller base to obtain a pre-treated base;
[0052] S3: placing the pretreated substrate into an ionic liquid pre-plating solution, performing pre-plating treatment, and obtaining a pre-plated substrate;
[0053] The composition of the ionic liquid pre-plating solution is: choline chloride-ethylene glycol ionic liquid as solvent, wherein the solvent contains 0.1 mol / L nickel chloride, 0.12 mol / L chromium chloride, 0.18 mol / L cobalt chloride, and 1.8 g / L lactic acid;
[0054] The working conditions of the pre-plating treatment are: current density 2mA / cm 2 , temperature is 78℃, time is 60min;
[0055] Choline chloride-ethylene glycol ionic liquid choline chloride and ethylene glycol are compounded in a molar ratio of 1:3;
[0056] S4: placing the pre-plated substrate into an ionic liquid electroplating solution containing modified nano-titanium carbide, and performing electroplating to obtain a substrate;
[0057] The composition of the ionic liquid electroplating solution is: choline chloride-ethylene glycol ionic liquid as solvent, wherein there are 0.1 mol / L nickel chloride, 0.21 mol / L chromium chloride, 0.1 mol / L cobalt chloride, 2 g / L lactic acid, and 4 g / L composite nano titanium carbide;
[0058] The working conditions of electroplating treatment are: current density 2mA / cm 2 , temperature is 78℃, time is 90min;
[0059] The preparation of the composite nano-titanium carbide comprises the following steps:
[0060] (1) mixing nano titanium dioxide, carbon black and nano boron carbide, ball milling, pre-pressing, gradient heating, furnace cooling, crushing and ball milling to obtain composite nano titanium carbide;
[0061] The mass ratio of nano-titanium dioxide, carbon black and nano-boron carbide is 3.1:6.2:1; the working conditions of pre-pressing are: pressure of 100MPa, time of 1min; the working conditions of gradient heating treatment are: in argon atmosphere, keep at 1150℃ for 90min, then heat to 1450℃ and keep for 30min;
[0062] (2) 2 g of composite nano-titanium carbide and 30 mL of N,N-dimethylformamide were mixed, 1 mmol of lanthanum nitrate hexahydrate, 1 mmol of cerium nitrate, and 25 mL of N,N-dimethylformamide were added, and 3 mmol of terephthalic acid and 25 mL of N,N-dimethylformamide were added. The mixture was transferred into a reaction kettle, kept at 110° C. for 46 h, cooled, filtered, washed, and dried to obtain composite nano-titanium carbide;
[0063] S5: performing low-temperature ion nitriding treatment on the base member, and then performing plasma electrolytic polishing, and drying to obtain a mirror roller;
[0064] The working conditions of low-temperature ion nitriding treatment are: first, hydrogen is introduced for sputtering for 30 minutes, then nitrogen and hydrogen are introduced in a volume ratio of 1:3, the furnace pressure is 420Pa, the temperature is 420℃, the time is 4h, and the furnace is cooled;
[0065] The working conditions of plasma electropolishing are: polishing voltage is 280V, electropolishing liquid temperature is 75℃, time is 2min, diving depth is 15cm; the composition of electropolishing liquid is: deionized water as solvent, containing 1mol / L phosphoric acid, 0.3mol / L methanol, and 5g / L sodium dodecyl sulfate.
[0066] Embodiment 3: The preparation process of the mirror surface roller comprises the following steps:
[0067] S1: alloy steel seamless steel pipe is used as the outer roller, Q345 is used as the inner cylinder, alloy steel is used as the shaft sleeve, the inner cylinder and the outer roller are welded to the shaft sleeve respectively, heat treated, and machined to obtain the mirror roller base;
[0068] The working conditions of heat treatment are: keep at 870℃ for 1h, then cool to 270℃ for 12h, and heat to 550℃ for 30min;
[0069] S2: Grinding, polishing, washing, alkali washing, acid washing, and ultrasonic washing the mirror roller base to obtain a pre-treated base;
[0070] S3: placing the pretreated substrate into an ionic liquid pre-plating solution, performing pre-plating treatment, and obtaining a pre-plated substrate;
[0071] The composition of the ionic liquid pre-plating solution is: choline chloride-ethylene glycol ionic liquid as solvent, wherein the solvent contains 0.1 mol / L nickel chloride, 0.12 mol / L chromium chloride, 0.18 mol / L cobalt chloride, and 1.8 g / L lactic acid;
[0072] The working conditions of the pre-plating treatment are: current density 2mA / cm 2 , temperature is 80℃, time is 60min;
[0073] Choline chloride-ethylene glycol ionic liquid choline chloride and ethylene glycol are compounded in a molar ratio of 1:3;
[0074] S4: placing the pre-plated substrate into an ionic liquid electroplating solution containing modified nano-titanium carbide, and performing electroplating to obtain a substrate;
[0075] The composition of the ionic liquid electroplating solution is: choline chloride-ethylene glycol ionic liquid as solvent, wherein there are 0.1 mol / L nickel chloride, 0.21 mol / L chromium chloride, 0.1 mol / L cobalt chloride, 2 g / L lactic acid, and 5 g / L composite nano titanium carbide;
[0076] The working conditions of electroplating treatment are: current density 2mA / cm 2 , temperature is 80℃, time is 90min;
[0077] The preparation of the composite nano-titanium carbide comprises the following steps:
[0078] (1) mixing nano titanium dioxide, carbon black and nano boron carbide, ball milling, pre-pressing, gradient heating, furnace cooling, crushing and ball milling to obtain composite nano titanium carbide;
[0079] The mass ratio of nano-titanium dioxide, carbon black and nano-boron carbide is 3.1:6.2:1; the working conditions of pre-pressing are: pressure of 100MPa, time of 1min; the working conditions of gradient heating treatment are: in argon atmosphere, keep at 1155℃ for 85min, then heat to 1455℃ for 25min;
[0080] (2) 2 g of composite nano-titanium carbide and 30 mL of N,N-dimethylformamide were mixed, 1 mmol of lanthanum nitrate hexahydrate, 1 mmol of cerium nitrate, and 25 mL of N,N-dimethylformamide were added, and 3 mmol of terephthalic acid and 25 mL of N,N-dimethylformamide were added. The mixture was transferred into a reaction kettle, kept at 112° C. for 44 h, cooled, filtered, washed, and dried to obtain composite nano-titanium carbide;
[0081] S5: performing low-temperature ion nitriding treatment on the base member, and then performing plasma electrolytic polishing, and drying to obtain a mirror roller;
[0082] The working conditions of low-temperature ion nitriding treatment are: first, hydrogen is introduced for sputtering for 30 minutes, then nitrogen and hydrogen are introduced in a volume ratio of 1:3, the furnace pressure is 420Pa, the temperature is 420℃, the time is 4h, and the furnace is cooled;
[0083] The working conditions of plasma electropolishing are: polishing voltage is 280V, electropolishing liquid temperature is 75℃, time is 2min, diving depth is 15cm; the composition of electropolishing liquid is: deionized water as solvent, containing 1mol / L phosphoric acid, 0.3mol / L methanol, and 5g / L sodium dodecyl sulfate.
[0084] Comparative Example 1: Example 3 was used as the control group, no pre-plating treatment was performed, and other processes were normal.
[0085] Comparative Example 2: Taking Example 3 as the control group, the modified nano-titanium carbide was replaced by composite nano-titanium carbide, and the other processes were normal.
[0086] Comparative Example 3: Example 3 was used as the control group, and no low-temperature ion nitriding treatment was performed, and other processes were normal.
[0087] Sources of raw materials used (for demonstration purposes only):
[0088] Alloy steel seamless steel pipe: by mass fraction, its element composition is: chromium 3.1%, nickel 2.9%, molybdenum 0.9%, vanadium 0.4%, carbon 0.4%, silicon 0.1%, copper 0.09%, aluminum 0.01%, the balance is iron; Q345: by mass fraction, its element composition is: chromium 0.3%, nickel 0.3%, molybdenum 0.9%, vanadium 0.04%, niobium 0.04%, carbon 0.14%, silicon 0.55%, manganese 1.4%, titanium 0.01%, copper 0.3%, aluminum 0.02%, the balance is iron; choline chloride C108896, ethylene glycol E103319, nickel chloride N112126, chromium chloride C113685, cobalt chloride C116457, lactic acid L108839, nano titanium dioxide T104946, carbon black C139969, nano boron carbide B591130, N,N-dimethylformamide D111999, lanthanum nitrate hexahydrate L106046, cerium nitrate C431279, terephthalic acid P 108506, sodium dodecyl sulfate S348686: Aladdin reagent; phosphoric acid, methanol, analytical grade: Sinopharm reagent.
[0089] Performance test: The mirror rollers prepared in the embodiments and comparative examples were tested:
[0090] Roughness test: Use TR200 roughness tester to test the surface roughness of the sample. Select 5 different positions on the surface of each sample for testing, and take the average value as the roughness result; Microhardness: Tested on a digital Vickers hardness tester, under a 2kg diamond indenter for 8s, each group of test points is 5, and the average value is taken as the microhardness; Wear resistance: Use a vertical universal friction and wear tester for testing, the grinding material is GCr15, the load is 10N, the turntable speed is 120r / min, the wear time is 1h, and the mass of the sample before and after wear is weighed for characterization; Corrosion resistance: Put the sample in a salt spray box, the temperature is 37℃, the sodium chloride concentration is 59g / L, the pH is 6.9, and observe whether there is surface rust after 15 days. If there is no rust, it is qualified, otherwise it is unqualified; The results are shown in Table 1;
[0091] Table 1
[0092] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Roughness Ra(nm) 9.2 9.2 9.1 / / / Hardness (HV) 722 724 727 625 610 616 Wear amount (mg) 0.32 0.32 0.31 0.37 0.61 0.57 Corrosion resistance qualified qualified qualified Failure Failure Failure
[0093] The present invention provides a mirror roller and a preparation process thereof. Through process and component design, a green and environmentally friendly mirror roller with good mechanical strength, high wear resistance and corrosion resistance is prepared. In Table 1, / indicates that the item has not been tested.
[0094] By comparing Example 3 with Comparative Examples 1 and 2, it can be seen that in order to improve the durability of the mirror roller in the present invention, an alloy steel seamless steel pipe is selected as the base material, and a green, environmentally friendly, conductive and highly stable choline chloride-ethylene glycol ionic liquid is used as the electroplating solvent. A nickel-chromium-cobalt coating is first pre-plated on the surface of the base as a transition layer, and then electroplating is continued on the transition layer to generate a modified nano-titanium carbide-doped nickel-chromium-cobalt surface, giving the mirror roller a gradient hardness, thereby greatly improving the wear resistance and corrosion resistance of the mirror roller; wherein the composite nano-titanium carbide is a composite titanium carbide that uses nano-titanium dioxide as a titanium source and synthesizes a high-purity, uniformly mixed titanium boride-titanium carbide composite ceramic nanopowder through a carbon thermal reduction reaction, and then a lanthanum and cerium double rare earth metal organic framework is in situ grown on the composite titanium carbide by a solvent thermal method, thereby increasing the movement rate of the modified titanium carbide in the ionic liquid, increasing the uniformity of its dispersion on the coating, and increasing the uniformity of the coating.
[0095] By comparing Example 3 with Comparative Example 1 and Comparative Example 3, it can be seen that in order to further improve the corrosion resistance and wear resistance of the mirror roller, the base member after electroplating is subjected to nitriding treatment, and clean, efficient, and workpiece-small deformation ion nitriding is selected for treatment. However, in the existing process, the ion nitriding temperature is usually higher than 450°C, which easily leads to the precipitation of chromium nitrides and reduces the corrosion resistance of the substrate. The existing low-temperature ion nitriding has problems such as low nitriding efficiency and long nitriding time, which is not conducive to the promotion of its process. In the present invention, because the modified titanium carbide introduced during electroplating contains titanium, lanthanum, and cerium, among which titanium is a strong nitride-forming element, the formation of chromium nitrides will be inhibited during the ion nitriding process, thereby ensuring the improvement of the corrosion resistance of the base member, and at the same time synergizing with the rare earth lanthanum and cerium to improve the nitriding efficiency, so that it can quickly improve the hardness, wear resistance and corrosion resistance of the mirror roller, which is conducive to its market promotion.
[0096] The above descriptions are only embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. The preparation process of the mirror roller is characterized in that: The following steps are involved: S1: alloy steel seamless steel pipe is used as the outer roller, Q345 is used as the inner cylinder, alloy steel is used as the shaft sleeve, the inner cylinder and the outer roller are welded to the shaft sleeve respectively, heat treated, and machined to obtain the mirror roller base; S2: Grinding, polishing, washing, alkali washing, acid washing, and ultrasonic washing the mirror roller base to obtain a pre-treated base; S3: placing the pretreated substrate into an ionic liquid pre-plating solution, performing pre-plating treatment, and obtaining a pre-plated substrate; S4: placing the pre-plated substrate into an ionic liquid electroplating solution containing modified nano-titanium carbide, and performing electroplating to obtain a substrate; S5: The base member is subjected to low temperature ion nitriding treatment, and then subjected to plasma electrolytic polishing and drying to obtain a mirror surface roller.
2. The process for preparing the mirror surface roller according to claim 1, characterized in that: The working conditions of heat treatment are: keep at 870℃ for 1h, then cool to 270℃ for 12h, and heat to 550℃ for 30min.
3. The process for preparing the mirror surface roller according to claim 1, characterized in that: The working conditions of low-temperature ion nitriding treatment are: first introduce hydrogen sputtering for 30 minutes, then introduce nitrogen and hydrogen with a volume ratio of 1:3, the furnace pressure is 420Pa, the temperature is 420℃, the time is 2h, and the furnace is cooled.
4. The process for preparing the mirror surface roller according to claim 1, characterized in that: The working conditions of plasma electropolishing are: polishing voltage is 280V, electropolishing liquid temperature is 75℃, time is 2min, diving depth is 15cm; the composition of electropolishing liquid is: deionized water as solvent, containing 1mol / L phosphoric acid, 0.3mol / L methanol, and 5g / L sodium dodecyl sulfate.
5. The process for preparing the mirror surface roller according to claim 1, characterized in that: The composition of the ionic liquid pre-plating solution is as follows: choline chloride-ethylene glycol ionic liquid is used as solvent, wherein the solution contains 0.1 mol / L nickel chloride, 0.12 mol / L chromium chloride, 0.18 mol / L cobalt chloride and 1.8 g / L lactic acid; the composition of the ionic liquid electroplating solution is as follows: choline chloride-ethylene glycol ionic liquid is used as solvent, wherein the solution contains 0.1 mol / L nickel chloride, 0.21 mol / L chromium chloride, 0.1 mol / L cobalt chloride, 2 g / L lactic acid and (3-5) g / L composite nano titanium carbide.
6. The process for preparing the mirror surface roller according to claim 5, characterized in that: The choline chloride-ethylene glycol ionic liquid is prepared by compounding choline chloride and ethylene glycol in a molar ratio of 1:
3.
7. The process for preparing the mirror surface roller according to claim 1, characterized in that: The working conditions of the pre-plating treatment are: current density 2mA / cm 2 , temperature is 75-80℃, time is 60min; electroplating working conditions are: current density 2mA / cm 2 , temperature is 75-80℃, time is 90min.
8. The process for preparing the mirror surface roller according to claim 1, characterized in that: The preparation of the modified nano titanium carbide comprises the following steps: (1) mixing nano titanium dioxide, carbon black and nano boron carbide, ball milling, pre-pressing, gradient heating, furnace cooling, crushing and ball milling to obtain composite nano titanium carbide; (2) Mix composite nano-titanium carbide and N,N-dimethylformamide, add a mixed solution of lanthanum nitrate hexahydrate, cerium nitrate, and N,N-dimethylformamide, add a mixed solution of terephthalic acid and N,N-dimethylformamide, transfer the mixture into a reaction kettle, keep the mixture at 108-112° C. for 44-48 hours, cool, filter, wash, and dry to obtain modified nano-titanium carbide.
9. The process for preparing the mirror surface roller according to claim 8, characterized in that: The mass ratio of nano-titanium dioxide, carbon black and nano-boron carbide is 3.1:6.2:1; the working conditions of pre-pressing are: pressure of 100MPa, time of 1min; the working conditions of gradient heating treatment are: in argon atmosphere, keep warm at 1145-1155℃ for 85-95min, then heat to 1445-1455℃ and keep warm for 25-35min.
10. Mirror roller, characterized in that: The invention is prepared by the preparation process described in any one of claims 1 to 9.